Farmer Empowerment in The Management of Rice Farming in Two Districts in West Java - Sadono, Dwi; Sumardjo, Sumardjo; Gani, Darwis S; Amanah, Siti (Journal of Rural Indonesia, 2014)
Efforts to integrated food security and farmer empowerment have become an important issue today. Accordingly, the objectives of this study were to analyze the level of participation of farmers in their group and the empowerment of farmers in the management of rice farming and the factors associated with it, and to analyze the impact of farmer empowerment on sustainability efforts. Fieldwork was conducted in May to June 2012 in two districts in West Java, by taking 239 farmers who had attended the farmer field school. Quantitative data were analyzed statistically based on the descriptive technique and Structural Equations Modeling (SEM). Qualitative data were collected through in-depth interview and observation to support the quantitative data. The results showed that: (1) The levels of farmer participation in the farmer group and the farmer empowerment were classified as low. The variables that significantly affected the levels of farmer participation in the farmer group were: intensity of empowerment and personality traits. The variables that significantly affected the levels of farmer empowerment were: farmer participation in the farmer group, intensity of empowerment, physical and socio-economic environment, personality traits, and availability of agricultural information. (2) The prospects for sustainability efforts were classified as low. The level of farmer empowerment significantly affected the sustainability of farming; and (3) The increasing level of farmer empowerment can be achieved by better management of empowerment process, with increasing farmer participation in the farmer group, strengthening the availability of agricultural information, and the physical and socio economic environment. Keywords: empowerment, participation, capacity of farmers, business sustainabilityReceived: 15th October 2014; Accepted: 15th November 2014[How to Cite: Sadono, D., Sumardjo, S., Gani, D., & Amanah, S. (2014). Farmer Empowerment in The Management of Rice Farming in Two Districts in West Java. Journal Of Rural Indonesia, 2(1), 105-120. Retrieved from http://ejournal.skpm.ipb.ac.id/index.php/ruralindonesia/article/view/297]